2021
DOI: 10.21037/atm-21-2589
|View full text |Cite
|
Sign up to set email alerts
|

CD73 expression in myeloid-derived suppressor cells is correlated with clinical stages in head and neck squamous cell carcinomas

Abstract: Background: Ecto-5'-nucleotidase (cluster of differentiation 73/CD73) is an ectonucleotidase that is being evaluated as a biomarker for the diagnosis and prognosis of various types of cancer. However, the clinicopathological relationship between CD73 expression in monocytic MDSCs (M-MDSCs) and polymorphonuclear MDSC (PMN-MDSCs) in head and neck squamous cell carcinomas (HNSCCs) is not clear. Understanding the phenotypic and functional characteristics of human CD73 + MDSCs in the tumor microenvironment could he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Approximately half a million patients are diagnosed annually with HNSC, and it is a major contributor to cancerrelated mortality worldwide [2]. The pathogenesis of HNSC is multifactorial [3,4], including (a) an acute demand for protein synthesis that is often a result of oncogene activation, (b) inadequate oxygen and nutrient supply as well as chemo/radiotherapy exposure, and (c) immune surveillance escape [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately half a million patients are diagnosed annually with HNSC, and it is a major contributor to cancerrelated mortality worldwide [2]. The pathogenesis of HNSC is multifactorial [3,4], including (a) an acute demand for protein synthesis that is often a result of oncogene activation, (b) inadequate oxygen and nutrient supply as well as chemo/radiotherapy exposure, and (c) immune surveillance escape [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the tumor state, MDSCs are abnormally produced and recruited to the TME to help establish an immunosuppressive TME and promote tumor angiogenesis and metastasis to support tumor progression. There are two main types of MDSCs, mononuclear MDSCs (M-MDSCs) and polymorphonuclear MDSCs (PMN-MDSCs) (134). In tumors, M-MDSC can quickly differentiate into TAMs (135,136), and the relationship between TAMs and ECs and the promotion of tumors have been discussed above.…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%
“…30 Data from both in vitro and in vivo studies suggest the presence of MDSC markers that correlate with cancer conditions in humans. 31,32 Translational studies have also demonstrated the predictive value of MDSCs in esophageal squamous cell carcinoma (ESCC) patients. 33 However, there is a shortage of published clinical data on MDSC-targeted cancer therapy due to the lack of novel MDSC targets.…”
Section: Tumor-induced Aberrations Of the Immune Environmentmentioning
confidence: 99%